On my horse - Greenfield, Eloise ([New York] : HarperFestival, 1995)
A boy riding slowly on a horse, sitting behind the horse's owner, imagines that he is riding swiftly by himself.
"Ages 2-5"--P. [4] of cover.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Imagination -- Fiction; African Americans -- Fiction; Stories in rhyme